Cereal Crops: Genetic Resources and Breeding Techniques - Shah, Tariq; Nie, Lixiao; Texeira Filho, Marcelo Carvalho Minhoto [UNESP]; Amir, Rabia (Taylor & Francis, 2023)
Cereal Crops: Genetic Resources and Breeding Techniques provides the reader practical tools for understanding relationships and challenges of successful farming; improvements to genetic modifications; and environmentally sound methods of production of bulk and quality cereals including wheat, maize, rice, barley, and millets. It explores the trait mapping, cropping systems, genome engineering, and identification of specific germplasms needed for the more effective development of biotic and abiotic stress resistant cereals within the framework of ensuring future food supplies around the world. Features: Focuses on cropping systems, genetics and genome engineering for higher crop production at a global level. Features information on specific prebiotic formulas to ward off adverse effects of antibiotics. Covers mechanistic as well as practical approaches for enhancing crop production in a sustainable way. Includes further in-depth analysis of various topics following each chapter. This is a vital resource for researchers, crop biologists, and students working with crop production and climate changes that have a significant impact on crop production, spanning basic to advanced level discussions of plant breeding, molecular genetics, and agronomy. Covering mechanistic and practical approaches for enhancing crop production in a sustainable way, this text is beneficial to intensive farmers and stakeholders in the field of crop production.